Shear dynamics in cholesterics - Orlandini, E; Marenduzzo, D; Yeomans, J (2005)
We study shear dynamic in cholesteric liquid crystal using a lattice Boltzmann scheme that solves the full, three-dimensional Beris-Edwards equations of hydrodynamics. We show that the coupling between shear and the natural elastic deformation of cholesterics can induce twist in an initially isotropic phase. (c) 2005 Elsevier B.V. All rights reserved.